Aluminum alloy composite material for brazing and manufacturing method thereof
By adopting a multi-layer structural design in the aluminum alloy composite material for brazing, optimizing the composition and thickness of each layer, and using a large amount of waste as raw materials, the problems of poor material performance and difficult waste to reuse in the prior art are solved, and high strength, good corrosion resistance and material self-circulation are achieved.
Patent Information
- Application Number
- CN202211663065.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-23
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-12-23
AI Technical Summary
While existing aluminum alloy composite materials for brazing consume more aluminum alloy waste, it is difficult to meet the requirements of brazing temperature, corrosion resistance and post-brazing strength, and waste with complex compositions is difficult to reuse as the production of aluminum brazing materials.
The aluminum alloy composite material for brazing using a multi-layer structure includes a core material layer, a first intermediate layer and a first brazing layer. The composition and thickness of the core material layer, the first intermediate layer and the first brazing layer are optimized, and more than 50% of waste is used as the raw material of the core material layer, and the plate-like alloy is formed by heat treatment and rolling, and finally softening and annealing is performed.
It is realized that when a large amount of waste is used, an aluminum alloy composite material with high strength and good corrosion resistance is obtained, which solves the problem of degradation in the performance of traditional waste-consuming alloys, and realizes the self-circulation of the material and reduces carbon emissions.
Smart Images

Figure CN115771311B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum brazing, in particular to an aluminum alloy composite material for brazing and a manufacturing method thereof. Background Art
[0002] Aluminum alloy has the characteristics of low density, good thermal conductivity, good electrical conductivity, and recyclability, and is widely used in various fields such as automobile transportation, construction, aerospace, and chemical industry. Aluminum brazing materials are also widely used in various automotive heat exchangers, such as water tanks, condensers, evaporators, and battery cold plates related to electric vehicles.
[0003] Aluminum brazing materials generally consist of a brazing layer, a core material and / or a water-contacting layer. The brazing layer usually uses an Al-Si alloy (Si content greater than 6%) as a brazing material. The brazing layer is completely melted at the brazing temperature (about 600°C), and the molten brazing material is adsorbed to the joint through the capillary action of the joint to achieve metallurgical bonding. The core alloy is generally AA3003 or its modified alloy, and the manganese content in the alloy is between 1.0-1.5wt%, while the Si content in the core material is generally low. The water-contacting layer alloy generally contains more than 1% Zn. In the process of preparing aluminum brazing materials, 30-40% of process waste is usually generated. These process wastes are mixed with different alloys such as brazing layers with high silicon content, core materials and water-contacting layers with high zinc content. On the whole, the process waste will contain higher contents of Si (≥1%) and Mn (≥1%), as well as elements such as Cu, Zn or Mg exceeding a certain amount. Since aluminum brazing materials must meet the requirements of 600-degree brazing, and in practical applications, there are certain requirements for corrosion resistance and strength after brazing, it is difficult to reuse waste materials with complex components to produce aluminum brazing materials, nor is it easy to prepare various aluminum alloys with existing standard components. At present, most aluminum alloy waste is directly downgraded and used to produce ordinary cast aluminum alloys. In addition, for various heat exchangers made of aluminum brazing materials, after the scrapping of automobiles, due to their complex components, it is almost difficult to recycle them into aluminum brazing materials, and they are basically used to make ordinary cast aluminum alloys. With the implementation of the "dual carbon" strategy and the improvement of carbon emission requirements in the aluminum processing industry, better utilization of these process wastes and post-consumer wastes (such as waste heat exchangers), recycling of wastes as raw materials, and the use of various wastes will be of great significance to the sustainable development of aluminum brazing materials, reducing the use of pure aluminum ingots and reducing carbon emissions.
[0004] Patent application CN112210700A discloses an Al-Mg-Mn-Si alloy. Compared with the traditional Al-Mg-Mn (5XXX) deformed aluminum alloy, its Si content is greatly increased (0.8-1.5%). The scrap aluminum of aluminum brazing materials produced in the field of heat transfer can be used as raw material. By strictly controlling the composition of elements in the alloy, good performance can be obtained. It can replace AA5052 alloy and has the advantage of low cost.
[0005] WO 2007 / 131727 A1 discloses a method for producing an aluminum alloy composite material for brazing, wherein the raw material for producing the core alloy contains at least 25 wt% of brazing sheet scrap. In order to avoid the reduction of corrosion resistance caused by the use of scrap, a small amount of Cr is intentionally added to the alloy. Summary of the invention
[0006] The current aluminum alloy composite materials for brazing consume more aluminum alloy waste (including process waste and post-consumer waste) and are difficult to meet the requirements of the product in actual use (such as requirements for brazing temperature, corrosion resistance, and strength after brazing). In order to solve the defects in the prior art, on the one hand, the present invention relates to an aluminum alloy composite material for brazing.
[0007] The brazing aluminum alloy composite material of the present invention comprises: a core material layer, a first brazing layer, and a first intermediate layer, wherein the first intermediate layer is located between the core material layer and the first brazing layer; based on the total weight of the core material layer, the core material layer comprises: 0.6-1.5 wt% Si, 0.1-1.0 wt% Cu, 0.2-2.0 wt% Mn, 0.05-0.5 wt% Mg, 1 wt% or less Fe, 0.2 wt% or less Sr; at least one of the following elements: 0.5 wt% or less Zn, 0.05-0.25 wt% Ti, 0.05-0.25 wt% Zr and 0.05-0.25 wt% Cr; the balance is Al and inevitable Impurities; Based on the total weight of the first intermediate layer, the first intermediate layer contains: 0.05-1.0 wt% Si, less than 0.6 wt% Fe, 0.5-2.0 wt% Mn, 0.1-2.5 wt% Zn; One or more of the following elements optionally present: less than 0.5 wt% Cu, less than 0.25 wt% Ti, less than 0.25 wt% Zr and less than 0.25 wt% Cr; the balance is Al and unavoidable impurities; Based on the total weight of the first brazing layer, the first brazing layer contains: 4-13 wt% Si, 0.05-2 wt% Cu, 0.05-6.00 wt% Zn, the balance is Al and unavoidable impurities.
[0008] In one embodiment, the aluminum alloy composite material for brazing of the present invention further comprises: a second intermediate layer, which is located on a side of the core material layer away from the first intermediate layer.
[0009] In another embodiment, the aluminum alloy composite material for brazing of the present invention further comprises: a second brazing layer, which is located on a side of the second intermediate layer away from the core material layer.
[0010] In one embodiment, based on the weight of the raw material of the core material layer in the brazing aluminum alloy composite material of the present invention, the raw material of the core material layer comprises more than 50% by weight of waste, wherein the waste is selected from: post-consumer waste, process waste and a combination thereof. In one embodiment, the post-consumer waste is waste generated after the heat exchanger containing the brazing aluminum alloy composite material is scrapped. In another embodiment, the process waste is waste generated during the preparation of the brazing aluminum alloy composite material.
[0011] On the other hand, the present invention also relates to a method for manufacturing the aluminum alloy composite material for brazing of the present invention, which comprises the following steps: preparing a core layer alloy, an intermediate layer alloy and a brazing layer alloy; subjecting the intermediate layer alloy to heat treatment and then rolling it into a plate to obtain a plate-like intermediate layer alloy; optionally subjecting the core layer alloy to heat treatment; rolling the brazing layer alloy into a plate to obtain a plate-like brazing layer alloy; stacking the plate-like intermediate layer alloy, the core layer alloy and the plate-like brazing layer alloy in sequence and then compounding them to obtain a composite; rolling the composite to a target thickness; and softening annealing. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 : A schematic structural diagram of an embodiment of the aluminum alloy composite material for brazing of the present invention;
[0013] Figure 2 : A schematic structural diagram of an embodiment of the aluminum alloy composite material for brazing of the present invention;
[0014] Figure 3 : A scanning electron microscope photograph of the first intermediate layer of Example 1 of the present invention, showing the particle distribution state therein;
[0015] Figure 4 : A scanning electron microscope photograph of the core material layer of Example 1 of the present invention, showing the particle distribution state therein;
[0016] Figure 5 : The morphology of the sample of the external corrosion test (SWAAT test) of Example 1 of the present invention;
[0017] Figure 6 : Morphology of the sample of the internal corrosion test (OY test) of Example 1 of the present invention
[0018] Reference numerals: 1 - core material layer; 2 - first intermediate layer; 2' - second intermediate layer; 3 - first brazing layer; 3' - second brazing layer. DETAILED DESCRIPTION
[0019] General Definitions and Terminology
[0020] Unless otherwise indicated, all publications, patent applications, patents, and other references mentioned herein are incorporated by reference in their entirety.
[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the definitions provided herein shall prevail. Unless otherwise indicated, all percentages, parts, ratios, etc. are by weight.
[0022] When quantity, concentration or other value or parameter is given as range, preferred range or preferred upper limit and lower limit or specific value, it should be understood as specifically disclosing all ranges formed by paired values from any upper limit range or preferred value and any lower limit range or preferred value, regardless of whether the range is disclosed separately. Unless otherwise stated, when numerical range is quoted herein, the range refers to including its endpoints and integers and fractions within all such ranges. The scope of the present invention is not limited to the specific numerical value quoted when defining the range. For example, "1-8" covers 1, 2, 3, 4, 5, 6, 7, 8 and any sub-range consisting of any two values therein, such as 2-6, 3-5.
[0023] The terms "about" and "approximately" when used with a numerical variable generally refer to the value of that variable and all values of that variable are within experimental error (e.g., within a 95% confidence interval for the mean) or within ±10% of the specified value, or a wider range.
[0024] The terms "comprises", "includes", "has", "contains" or "involves" and other variations thereof herein are inclusive or open-ended and do not exclude other unlisted elements or method steps. It will be understood by those skilled in the art that the above terms such as "comprising" encompass the meaning of "consisting of". The expression "consisting of" excludes any element, step or ingredient not specified. The expression "consisting essentially of" means that the scope is limited to the specified elements, steps or ingredients, plus the optional presence of elements, steps or ingredients that do not substantially affect the basic and novel features of the claimed subject matter. It will be understood that the expression "comprising" encompasses the expressions "consisting essentially of" and "consisting of".
[0025] The term "selected from..." means that one or more elements in the group listed later are independently selected and may include combinations of two or more elements.
[0026] When values or end-points of a range are described herein, it should be understood that the disclosure includes the specific value or end-point cited.
[0027] As used herein, the terms "one or more" or "at least one" refer to one, two, three, four, five, six, seven, eight, nine or more.
[0028] Unless otherwise specified, the terms "combination thereof" and "mixture thereof" refer to a multi-component mixture of the elements, such as a two-component mixture, a three-component mixture, a four-component mixture and the maximum possible multi-component mixture.
[0029] In addition, if the number of parts or components of the present invention is not indicated before, it means that there is no limit to the number of occurrences (or existence) of the parts or components. Therefore, it should be interpreted as including one or at least one, and the singular form of the parts or components also includes the plural form, unless the numerical value obviously represents the singular.
[0030] As used herein, the term "optional" or "optionally" means that the subsequently described event or circumstance may or may not occur, and that the description includes both occurring and not occurring of said event or circumstance.
[0031] The term "inevitable impurity elements" used herein refers to elements that are not actively added during the preparation of aluminum alloys and are inevitably introduced into the alloys. "Other elements" refers to elements that are not included in the corresponding alloys.
[0032] The term "dispersed particle phase" used herein refers to the precipitation of elements such as Si, Mn, Cu dissolved in the solid solution from the solid solution during the thermomechanical processing to form a small, widely distributed particle phase, which is different from the casting particle phase. In this article, the dispersed particle phase mainly refers to the particle phase of Al-Mn (Cu) -Si. The size and distribution of these particle phases can be observed and measured by scanning electron microscope.
[0033] The term "casting particle phase" used herein refers to a larger particle phase formed during the solidification process of the ingot. The casting particle phase may remain unchanged or be broken to a certain extent during the subsequent thermomechanical processing, but the size of the broken particles exceeds 1 μm.
[0034] The term "solid solution" as used herein refers to an alloy phase in which solute atoms are dissolved in a solvent lattice while still maintaining a solvent type. In this article, solid solution mainly refers to alloying elements such as Si, Cu, Mn, etc., which are "solidified" in the aluminum phase due to the rapid cooling rate during the casting process and do not have time to precipitate from the solidified aluminum phase. The supersaturated solid solution will cause solute atoms such as Si, Cu, and Mn to precipitate from the solid solution during the subsequent thermomechanical processing to form a dispersed particle phase.
[0035] The term "P-oriented texture" as used herein refers to the crystallographic orientation of the recrystallized grains formed after brazing of the composite material to be P-oriented ({011} <111> ), this preferred orientation of grains is called P-oriented texture. "Rotated cubic texture" refers to the crystallographic orientation of the recrystallized grains formed after brazing of the composite material is rotated cubic orientation (({001} <110> )). Texture can be measured by electron backscatter diffraction (EBSD).
[0036] The term "equivalent diameter" used herein refers to the diameter of a circular particle of equal area to the area of an irregularly shaped particle, and may also be referred to as the "circular diameter". In this article, the equivalent diameter of a dispersed particle phase may also be referred to as the size of the dispersed particle phase.
[0037] The term "composite ratio" used herein refers to the ratio of the thickness of each layer to the total thickness of the composite material. Taking the core material layer as an example, the composite ratio of the core material layer is the ratio of the thickness of the core material layer to the total thickness of the composite material. For the composite material of the present invention, the density of each layer (core material layer, intermediate layer, brazing layer) is almost the same, therefore, the composite ratio can also refer to the ratio of the thickness of each layer to the total weight of the composite material. Taking the core material layer as an example, the composite ratio of the core material layer is the ratio of the weight of the core material layer to the total weight of the composite material.
[0038] Aluminum alloy composite materials for brazing
[0039] In one aspect, the present invention relates to an aluminum alloy composite material for brazing, comprising: a core material layer, a first brazing layer, and a first intermediate layer, wherein the first intermediate layer is located between the core material layer and the first brazing layer. The structure of the aluminum alloy composite material for brazing can be as follows Figure 1 As shown, it comprises: a core material layer 1, a first intermediate layer 2 and a first brazing layer 3.
[0040] The aluminum alloy composite material for brazing of the present invention may further include a second intermediate layer, which is located on the side of the core material layer away from the first intermediate layer. Figure 2 As shown, the brazing aluminum alloy composite material comprises: a core material layer 1, a first intermediate layer 2, a second intermediate layer 2' and a first brazing layer 3. The brazing aluminum alloy composite material may further comprise a second brazing layer, which is located on the side of the core material layer away from the first intermediate layer.
[0041] The thickness of the brazing aluminum alloy composite material is related to the number of layers, and needs to be adjusted considering the thickness of each layer. When the thickness is too small, it is not conducive to meeting the requirements for the strength and corrosion resistance of the composite material. In one embodiment, the thickness of the brazing aluminum alloy composite material is 0.15-3 mm, for example, 0.2 mm, 0.25 mm.
[0042] The form of the aluminum alloy composite material for brazing can be processed according to actual needs, including but not limited to plates and strips.
[0043] In one embodiment, the aluminum alloy composite material for brazing is a layered brazing composite plate.
[0044] Core layer
[0045] The core layer is one of the main structures of aluminum alloy composite materials for brazing, and its characteristics (such as hardness, strength, toughness, etc.) will affect the performance of the composite material.
[0046] In the aluminum alloy composite material for brazing of the present invention, based on the total weight of the core material layer, the core material layer contains: 0.6-1.5 weight % Si, 0.1-1.0 weight % Cu, 0.2-2.0 weight % Mn, 0.05-0.5 weight % Mg, 1 weight % or less Fe, 0.2 weight % or less Sr; at least one of the following elements: 0.5 weight % or less Zn, 0.05-0.25 weight % Ti, 0.05-0.25 weight % Zr and 0.05-0.25 weight % Cr; the balance is Al and unavoidable impurities.
[0047] Si in the core material layer has an important influence on the performance of the composite material. In the core material, Si forms AlFeMnSi series compounds together with Fe and Mn, which plays a role of dispersion strengthening. Si can react with Mg to form Mg2Si compounds, thereby improving the strength of the composite material. In addition, Si can be dissolved in the core material matrix to improve the strength of the material through solid solution strengthening. Based on the total weight of the core material layer, the Si content in the core material layer can be 0.6-1.5% by weight, preferably 0.8-1.2% by weight, for example, about 0.83% by weight, about 0.92% by weight, about 1.11% by weight, etc. If the Si content is too low, the strengthening effect it produces becomes worse; if the Si content is too high, the melting point of the core material is reduced, increasing the possibility of overburning, and a low melting point eutectic phase may be formed.
[0048] The inclusion of an appropriate amount of Mn in the core material layer helps to improve the strength, brazing properties, corrosion resistance and electrical potential of the material. Based on the total weight of the core material layer, the Mn content in the core material layer can be 0.2-2.0% by weight, preferably 0.5-1.8% by weight, for example, about 1.16% by weight, about 1.33% by weight, about 1.49% by weight, etc. When the Mn content is too low, the advantages it brings are not obvious; when the Mn content is too high, coarse Mn-containing particles will be formed, which will affect the rolling production and cause holes or broken strips to form in the material.
[0049] The Mg element can significantly improve the strength of the alloy, and achieve the effect of improving strength through solid solution strengthening or through precipitation of Mg2Si. Based on the total weight of the core layer, the Mg content in the core layer can be 0.05-0.5% by weight, preferably 0.05-0.35% by weight, such as about 0.12% by weight, about 0.08% by weight, about 0.20% by weight, etc. When the Mg content is too low, its technical effect is weak. When the Mg content is too high, Mg may diffuse and volatilize during the brazing process, which has an adverse effect on the activity of the brazing agent, thereby causing the brazing effect to deteriorate; excessive Mg is also prone to intergranular corrosion.
[0050] The Fe element can be combined with other elements, such as Mn and Si, to form a casting crystalline phase, which can become an intermetallic compound of the size of a recrystallization nucleus, thereby reducing the recrystallization temperature. Based on the total weight of the core layer, the Mg content in the core layer can be less than 1 wt%, preferably less than 0.6 wt%, such as 0.32 wt%, 0.38 wt%, 0.57 wt%, etc., so as to ensure that the material has good formability and corrosion resistance. Too high a Fe content may reduce the corrosion resistance of the composite material and also reduce the strength of the material.
[0051] Cu can improve the strength of the core material layer by solid solution strengthening and can improve the potential. Based on the total weight of the core material layer, the content of Cu in the core material layer can be 0.1-1.0% by weight, preferably 0.3-0.8% by weight, for example, about 0.87% by weight, about 0.59% by weight, about 0.34% by weight, etc. If the content of Cu in the core material layer is too low, the advantageous effect it brings is not obvious; if the Cu content is too high, the possibility of intergranular corrosion becomes higher and may significantly affect the melting point.
[0052] Sr is often added to Al-Si alloys as a modifier. Adding an appropriate amount of Sr can refine the cast structure and improve the corrosion resistance through its diffusion or precipitation at the grain boundary. Based on the total weight of the core layer, the content of Sr in the core layer is 0.2 weight % or less, preferably 0.15 weight % or less.
[0053] Ti improves strength by solid solution strengthening and improves corrosion resistance. Based on the total weight of the core layer, the content of Ti in the core layer is 0.25 wt% or less, preferably 0.15 wt% or less, for example, about 0.08 wt%, 0.11 wt%, 0.09 wt%, etc. When the content of Ti is too high, it is easy to form a huge intermetallic compound, which reduces plastic workability.
[0054] Zr is added as an alloying element to further improve the strength of the alloy after brazing and to control the size of recrystallized grains. Based on the total weight of the core layer, the content of Zr in the core layer may be 0.25 wt% or less, preferably 0.15 wt% or less, for example, about 0.02 wt%, about 0.03 wt%, etc.
[0055] The addition of Cr as an alloying element can further improve the strength and corrosion resistance of the alloy after brazing. Based on the total weight of the core layer, the content of Cr in the core layer can be 0.25 wt % or less, preferably 0.2 wt % or less, for example, about 0.01 wt %.
[0056] The thickness of the core material layer can be selected according to actual needs. Generally speaking, the thickness should not be too thin. The thickness of the core material layer can be 50-90% of the brazing aluminum alloy composite material, such as 50%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, etc., so that the final composite material can obtain suitable properties (such as strength, hardness, deformation resistance, etc.).
[0057] By controlling the density of the dispersed particle phase with an equivalent diameter of 0.01-0.3 μm in the core material layer, the solid solubility of the Mn element can be reduced, which is conducive to the nucleation of grains with a specific orientation, thereby giving the aluminum alloy composite material a certain texture strengthening effect. The density of the dispersed particle phase with an equivalent diameter of 0.01-0.3 μm in the core material layer of the present invention can be 5×10 9 -6×10 10 Pieces / mm 3 , for example, about 2.1×10 10 Pieces / mm 3 , about 1.8×10 10 Pieces / mm 3 , about 5.3×10 10 Pieces / mm 3 , about 2.3×10 10 Pieces / mm 3 , about 4.1×10 10 Pieces / mm 3 , about 5.0×10 9 Pieces / mm 3 , about 6.0×10 9 Pieces / mm 3 , about 8.0×10 9 Pieces / mm 3 , about 1.0×10 10 Pieces / mm 3 , about 2.0×10 10 Pieces / mm 3 , about 3.0×10 10 Pieces / mm 3 , about 5.0×1010 Pieces / mm 3 , about 6.0×10 10 Pieces / mm 3 wait.
[0058] Middle Layer
[0059] In the brazing aluminum alloy composite material of the present invention, the intermediate layer is located on one side or both sides of the core material layer. The intermediate layer may include a first intermediate layer, based on the total weight of the first intermediate layer, the first intermediate layer contains: 0.05-1.0 wt% Si, 0.6 wt% or less Fe, 0.5-2.0 wt% Mn, 0.1-2.5 wt% Zn; one or more of the following elements optionally present: 0.5 wt% or less Cu, 0.25 wt% or less Ti, 0.25 wt% or less Zr and 0.25 wt% or less Cr; the balance is Al and unavoidable impurities.
[0060] Si can form AlMnSi dispersed phase particles together with Mn, which plays a role in dispersion strengthening. The fine dispersed particles can control the recrystallization process and affect the size and orientation of the recrystallized grains. Based on the weight of the first intermediate layer, the content of Si in the first intermediate layer can be 0.05-1.0% by weight, preferably 0.2-0.7% by weight, for example, about 0.65% by weight, 0.85% by weight. If the Si content is too low, the technical effect it brings is not obvious; if the Si content is too high, it significantly affects the composition and size of the dispersed phase particles, which may lead to a weakening of the strengthening effect of the particles and the influence on the grain structure.
[0061] Mn is the basis for forming various particles. Mn-containing dispersed particles will affect the recrystallization process of grains during brazing. An appropriate content of Mn can improve the strength and corrosion resistance of the material. Based on the weight of the first intermediate layer, the Mn content in the first intermediate layer can be 0.5-2.0% by weight, preferably 0.8-1.8% by weight, more preferably 1.0-1.6% by weight, for example, about 1.45% by weight, about 1.28% by weight.
[0062] Fe is a common impurity element in aluminum alloys. Fe forms intermetallic compounds in aluminum, which reduces the corrosion resistance. In the first intermediate layer, the content of Fe should be less than 0.6 weight %, for example, about 0.27 weight %, 0.25 weight %, to ensure the performance of the material.
[0063] The Cu element, as a strengthening or hardening component, improves strength through solid solution strengthening and can increase potential. The Cu content in the first intermediate layer should be less than 0.5 wt%, for example, about 0.21 wt%, about 0.07 wt%. If the Cu content is too high, intergranular corrosion is likely to occur.
[0064] The appropriate content of Zn can reduce the electrode potential of the intermediate layer, inhibit local pitting corrosion, and achieve a uniform corrosion effect. The content of Zn in the first intermediate layer can be 0.1-2.5% by weight, preferably 0.5-2.0% by weight, for example, about 2.47% by weight, about 0.04% by weight. When the content of Zn is too low, the effect of inhibiting pitting corrosion is weak; when the content of Zn is too high, the uniform corrosion sensitivity is too strong, which is not conducive to the performance of the composite material.
[0065] When the content of Ti, Zr and Cr in the first intermediate layer is too high, it is easy to form a huge intermetallic compound, which reduces the plastic workability. In the first intermediate layer, the content of Ti, Zr and Cr should be less than 0.25 wt%, preferably less than 0.15 wt%.
[0066] The intermediate layer of the present invention may further include a second intermediate layer, which is located on the side of the core material layer away from the first intermediate layer. Based on the total weight of the second intermediate layer, the second intermediate layer may contain: 0.05-1.0 wt% Si, 0.6 wt% or less Fe, 0.5-2.0 wt% Mn, 0.1-2.5 wt% Zn; one or more of the following elements optionally present: 0.5 wt% or less Cu, 0.25 wt% or less Ti, 0.25 wt% or less Zr and 0.25 wt% or less Cr; the balance is Al and unavoidable impurities.
[0067] In the present invention, it is most critical to control the number and size of particles in the intermediate layer. The dispersed particle phase with an equivalent diameter of 0.01-0.3 μm can not only provide particle strengthening, but also hinder the movement of dislocations, subgrain boundaries and grain boundaries, thereby coarsening the grains. This coarsened grain structure is very helpful in inhibiting the penetration of the brazing layer during brazing. The density of the dispersed particle phase of 0.01-0.3 μm in the intermediate layer alloy is relatively high, which can reduce the solid solubility of the Mn element, help the nucleation of grains with a specific orientation, and make the composite material produce a certain texture strengthening effect. The number and size of particles in the intermediate layer can be controlled by heat treatment. In one embodiment, the density of the dispersed particle phase with an equivalent diameter of 0.01-0.3 μm in the first intermediate layer is 1×10 10 -5×10 11 Pieces / mm 3 , preferably 7.5×10 10 -3.1×10 11 Pieces / mm 3 , for example, about 1.9×10 11 Pieces / mm 3 , about 8.5×10 10 Pieces / mm 3 , about 2.2×10 11 Pieces / mm 3 , about 8.1×10 10Pieces / mm 3 , about 9.2×10 10 Pieces / mm 3 , about 5.0×10 10 Pieces / mm 3 , about 1.0×10 11 Pieces / mm 3 , 2.0×10 11 Pieces / mm 3 , 3.0×10 11 Pieces / mm 3 4.0×10 11 Pieces / mm 3 , 5.0×10 11 Pieces / mm 3 In another embodiment, the density of the dispersed particle phase with an equivalent diameter of 0.01-0.3 μm in the second intermediate layer is 1×10 10 -5×10 11 Pieces / mm 3 , for example, about 1.3×10 11 Pieces / mm 3 , about 9.9×10 10 Pieces / mm 3 , about 9.4×10 10 Pieces / mm 3 , about 5.0×10 10 Pieces / mm 3 , about 1.0×10 11 Pieces / mm 3 , 2.0×10 11 Pieces / mm 3 , 3.0×10 11 Pieces / mm 3 4.0×10 11 Pieces / mm 3 , 5.0×10 11 Pieces / mm 3 wait.
[0068] For a specific range of Mn content in the interlayer, the appropriate number and size properties of the interlayer particles can significantly improve the performance of the product. When the interlayer contains 1.0-1.5 wt% Mn, the density of the dispersed particle phase with an equivalent diameter of 0.01-0.3 μm in the interlayer can be 7.5×10 10 -3.1×10 11 Pieces / mm 3The obtained composite material has better properties (such as mechanical strength, corrosion resistance, etc.). In one embodiment, the first intermediate layer contains 1.0-1.5 wt% Mn based on the weight of the first intermediate layer, and the density of the dispersed particle phase with an equivalent diameter of 0.01-0.3 μm in the first intermediate layer is 7.5×10 10 -3.1×10 11 Pieces / mm 3 In another embodiment, the second intermediate layer comprises 1.0-1.5 wt% Mn based on the weight of the second intermediate layer, and the density of the dispersed particle phase with an equivalent diameter of 0.01-0.3 μm in the second intermediate layer is 7.5×10 10 -3.1×10 11 Pieces / mm 3 .
[0069] The ratio of the density of the dispersed particle phase of 0.01-0.3 μm in the intermediate layer and the core material layer will affect the performance of the composite material. If the ratio is too low, the strength of the material will be reduced and the composition of the microstructure will be destroyed. The particle density ratio of the dispersed particle phase with an equivalent diameter of 0.01-0.3 μm in the first intermediate layer to the dispersed particle phase with an equivalent diameter of 0.01-0.3 μm in the core material layer can be 1-10, such as 1, 2, 2.2, 3, 3.5, 4, 4.1, 4.7, 5, 6, 7, 8, 9, 10, etc. The particle density ratio of the dispersed particle phase with an equivalent diameter of 0.01-0.3 μm in the second intermediate layer to the dispersed particle phase with an equivalent diameter of 0.01-0.3 μm in the core material layer is 1-10, such as 1, 2, 2.2, 3, 3.5, 4, 4.1, 4.7, 5, 6, 7, 8, 9, 10, etc.
[0070] By controlling the density and density ratio of the dispersed particle phase of 0.01-0.3 μm in the intermediate layer and the core layer, the aluminum alloy composite material can be given a texture strengthening effect, so that the total proportion of P texture and rotated cubic texture of the aluminum brazing composite material after brazing is more than 45%.
[0071] The thickness of the appropriate intermediate layer can effectively inhibit the penetration of the brazing layer. In one embodiment, the thickness of the first intermediate layer accounts for 5%-20% of the total thickness of the brazing aluminum alloy composite material. In another embodiment, the thickness of the second intermediate layer accounts for 5%-20% of the total thickness of the brazing aluminum alloy composite material. If the thickness of the intermediate layer accounts for too high a proportion, the strength of the composite material decreases; if the thickness of the intermediate layer accounts for too low a proportion, the penetration of the brazing layer cannot be effectively inhibited, thereby damaging the corrosion resistance of the material.
[0072] Brazing layer
[0073] In the aluminum alloy composite material for brazing of the present invention, the brazing layer may cover the outer surface of the intermediate layer (the first intermediate layer and / or the second intermediate layer) to impart brazing properties to the composite material.
[0074] In one embodiment, the brazing layer comprises a first brazing layer, which is located on the outer surface of the first intermediate layer, that is, the side of the first intermediate layer facing away from the core material layer. Based on the total weight of the first brazing layer, the first brazing layer may contain: 4-13 wt% Si, 0.05-2 wt% Cu, 0.05-6.00 wt% Zn, and the balance is Al and unavoidable impurities.
[0075] In another embodiment, the brazing layer further comprises a second brazing layer, which is located on the side of the second intermediate layer away from the core material layer. Based on the total weight of the second brazing layer, the second brazing layer may contain: 4-13 wt% Si, 0.05-2 wt% Cu, 0.05-6.00 wt% Zn, and unavoidable impurities each containing less than 0.05 wt% and a total content of less than 0.15 wt%; the balance is Al.
[0076] In one embodiment, the braze layer (the first braze layer and / or the second braze layer) is AA4343, AA4045, or a combination thereof.
[0077] The thickness of the brazing layer will affect the brazing performance of the composite material. Too thin or too thick is not conducive to giving the composite material a good brazing effect. In one embodiment, the thickness of the first brazing layer accounts for 5%-15% of the total thickness of the brazing aluminum alloy composite material. In another embodiment, the thickness of the second brazing layer accounts for 5%-15% of the total thickness of the brazing aluminum alloy composite material.
[0078] Raw materials for each layer
[0079] The raw material of the core material layer refers to the material used to prepare the core material layer. The raw material of the core material layer can be an alloy ingot formed by melting various materials. Using waste materials as the raw material of the core material layer can improve the sustainable development efficiency of aluminum brazing materials and achieve a more green and environmentally friendly goal. The core material layer is the main part of the composite material, that is, the weight of the core material layer accounts for a relatively high proportion of the total weight of the composite material. Therefore, the raw material of the core material layer contains a certain proportion of waste materials, which can significantly improve the recycling efficiency of the waste materials, which is of great significance to the goal of environmental protection.
[0080] Accordingly, the raw material of the intermediate layer refers to the material used to prepare the intermediate layer, and the raw material of the brazing layer refers to the material used to prepare the brazing layer.
[0081] Waste materials are usually recycled materials. Therefore, compared with non-recycled alloy materials (such as commercially available aluminum alloy materials), the element composition in the waste materials is usually more complex, and usually contains higher contents of elements such as Si and Mn. However, for composite materials, the content of elements in each layer (such as Si, Mn) needs to be controlled within a suitable range, and too high an element content may have an adverse effect on the performance of the product. In the present invention, by using a multilayer structure to replace the traditional two-layer or three-layer material, and optimizing the composition and proportion of each layer of material in the composite material, a material with both high strength and good corrosion resistance can be obtained. The strength and corrosion resistance of the composite material are further improved by regulating the microstructure in the core layer and the intermediate layer. Therefore, the present invention can ensure the performance of the composite material obtained while using more waste materials as the raw materials for each layer.
[0082] Waste can be post-consumer waste, process waste or a combination of the two. Process waste refers to the waste that is generated during the production and processing process due to the limited yield rate. This part of waste is called process waste. Post-consumer waste refers to the waste generated when products containing aluminum brazing materials (such as heat exchangers) are scrapped. This part of waste is called post-consumer waste.
[0083] When the waste contains high Si and Mn content or complex elements, it will increase the difficulty of recycling the waste. The composite material obtained by the design of the present invention can consume more waste in the preparation process while ensuring the material performance.
[0084] The post-consumer waste that can be used in the present invention may contain one or more of the following elements: 0.8-1.8 wt% Si, 1.0-1.6 wt% Mn. The post-consumer waste may also optionally contain one or more of the following elements: 0.1-0.6 wt% Cu, 0.2-0.7 wt% Zn, 0.02-0.15 wt% Mg. The process waste that can be used in the present invention contains one or more of the following elements: 0.7-3.0 wt% Si, 0.8-1.5 wt% Mn. The process waste may also optionally contain one or more of the following elements: 0.1-0.6 wt% Cu, 0.03-1.3 wt%, Zn and 0.02-0.5 wt% Mg.
[0085] In one embodiment, based on the total weight of the raw materials of the core material layer, the raw materials of the core material layer include more than 70 wt% of waste, for example, 50-70 wt% of waste, such as 50 wt%, 52 wt%, 55 wt%, 56 wt%, 60 wt%, 65 wt%, etc. The amount of waste included is too low to effectively improve the recycling rate of waste, thereby reducing the efficiency of sustainable development of aluminum brazing materials.
[0086] In one embodiment, the raw materials of the core layer contain more than 20 wt% post-consumer waste, for example, 20-35 wt% post-consumer waste is added, such as 20 wt%, 21 wt%, 24 wt%, 28 wt%, 30 wt%, 32 wt%, 35 wt%, etc., of process waste, based on the total weight of the raw materials of the core layer.
[0087] In another embodiment, the raw materials of the core layer contain more than 25 wt % of process waste, for example, 25-40 wt % of process waste is added, such as 25 wt %, 30 wt %, 31 wt %, 32 wt %, 33 wt %, 35 wt %, 40 wt % and the like of process waste is added, based on the total weight of the raw materials of the core layer.
[0088] In one embodiment, the post-consumer waste may be waste generated after the product comprising the brazing aluminum alloy composite material of the present invention is scrapped. In one embodiment, during the preparation process, the added post-consumer waste may be waste generated after the heat exchanger comprising the brazing aluminum alloy composite material of the present invention is scrapped. In another embodiment, the process waste may be waste generated during the preparation of the brazing aluminum alloy composite material of the present invention.
[0089] Manufacturing of aluminum alloy composite materials for brazing
[0090] In another aspect, the present invention relates to a method for manufacturing the aluminum alloy composite material for brazing of the present invention, comprising the following steps:
[0091] preparing a core layer alloy, an intermediate layer alloy and a brazing layer alloy;
[0092] The intermediate layer alloy is heat treated and then rolled into a plate to obtain a plate-shaped intermediate layer alloy; the core layer alloy is optionally heat treated; the brazing layer alloy is rolled into a plate-shaped brazing layer alloy;
[0093] After stacking the plate-shaped intermediate layer alloy, the core material layer alloy and the plate-shaped brazing layer alloy in sequence, they are compounded to obtain a composite body;
[0094] rolling the composite body to a target thickness;
[0095] Softening annealing.
[0096] By selecting appropriate raw materials, smelting and casting, a core layer alloy, an intermediate layer aluminum alloy and a brazing layer alloy having the composition described above are obtained. The inventors have found that by controlling the composition (e.g., the types and contents of the elements contained) and microscopic composition (e.g., the density and size properties of dispersed phase particles) of the core layer, the intermediate layer and the brazing layer, and by rationally designing the structure of the composite material (e.g., using the multilayer structure described above), a certain proportion of waste can be added during the preparation of the core layer alloy, the intermediate layer alloy and the brazing layer alloy, thereby achieving the goal of green environmental protection and sustainability while ensuring that the prepared composite material has good performance (e.g., excellent corrosion resistance and high strength). This solves the problem of performance degradation or downgrade of traditional waste-consuming alloys due to the addition of waste.
[0097] In the preparation process of the present invention, the waste material added may be: process waste, post-consumer waste or a combination thereof, wherein "waste material", "process waste" and "post-consumer waste" are as described above.
[0098] In one embodiment, based on the weight of the core layer alloy, more than 50% by weight of waste is added during the preparation of the core layer alloy, for example, 50-70% by weight of waste is added, such as 50%, 52%, 55%, 56%, 60%, 65%, etc. If the amount of waste added is too low, the recovery rate of the waste cannot be effectively improved, and the efficiency of sustainable development of aluminum brazing materials is reduced.
[0099] In one embodiment, based on the weight of the core layer alloy, more than 25 wt % of process waste is added during the preparation of the core layer alloy, for example, 25-40 wt % of process waste is added, such as 25 wt %, 30 wt %, 31 wt %, 32 wt %, 33 wt %, 35 wt %, 40 wt %, etc. of process waste is added.
[0100] In one embodiment, more than 20 wt. % post-consumer scrap is added during the preparation of the core layer alloy, for example, 20-35 wt. % post-consumer scrap is added, such as 20 wt. %, 21 wt. %, 24 wt. %, 28 wt. %, 30 wt. %, 32 wt. %, 35 wt. %, etc., of process scrap, based on the weight of the core layer alloy.
[0101] The post-consumer waste usable in the present invention may contain one or more of the following elements: 0.8-1.8 wt% Si, 1.0-1.6 wt% Mn. The post-consumer waste may also optionally contain one or more of the following elements: 0.1-0.6 wt% Cu, 0.2-0.7 wt% Zn, 0.02-0.15 wt% Mg.
[0102] The process waste material useful in the present invention comprises one or more of the following elements: 0.7-3.0 wt. % Si, 0.8-1.5 wt. % Mn. The process waste material may also optionally comprise one or more of the following elements: 0.1-0.6 wt. % Cu, 0.03-1.3 wt. % Zn and 0.02-0.5 wt. % Mg.
[0103] The inventors have found that the composite material obtained by the design of the present invention, its own process waste (i.e., waste generated in the process of preparing the composite material of the present invention) and post-consumer waste (i.e., waste generated after the product (such as a heat exchanger) using the composite material of the present invention is scrapped) can also be fully recycled without generating additional unusable waste. The process waste and post-consumer waste of the composite material of the present invention can be used again to prepare the composite material (such as the core material layer) of the present invention. That is, the aluminum alloy composite material for brazing of the present invention can achieve self-circulation of the material. Therefore, the composite material prepared by the present invention can achieve green and sustainable development, can significantly reduce carbon emissions, and create conditions for achieving the dual carbon strategy.
[0104] In one embodiment, during the preparation process, the added post-consumer waste may be waste generated after the product comprising the brazing aluminum alloy composite material of the present invention is scrapped. In one embodiment, during the preparation process, the added post-consumer waste may be waste generated after the heat exchanger comprising the brazing aluminum alloy composite material of the present invention is scrapped. In another embodiment, during the preparation process, the process waste may be waste generated during the preparation of the brazing aluminum alloy composite material of the present invention.
[0105] After the intermediate layer alloy is heat treated, it is rolled into a plate shape to obtain a plate-shaped intermediate layer alloy. Through appropriate heat treatment, the desired microstructure can be formed in the intermediate layer alloy, uniformly sized and tiny particles can be obtained, and the density of the dispersed particle phase of 0.01-0.3μm can be controlled. If the heat treatment temperature is too high, the particles will coarsen; if the heat treatment temperature is too low, the precipitation of particles will be difficult, which is not conducive to obtaining the desired density of the dispersed particle phase of 0.01-0.3μm. In one embodiment, the heat treatment temperature of the intermediate layer alloy is 350-550℃, preferably 450-550℃. In one embodiment, the heat treatment time of the intermediate layer alloy is 2-15 hours. Optionally, the core layer alloy can be heat treated. In one embodiment, the core layer alloy ingot is heat treated. In one embodiment, the heat treatment temperature of the core layer alloy is 450-550℃, preferably 480-550℃. The brazing layer alloy does not require an additional heat treatment process and can be directly used in the subsequent process after being rolled into a plate shape. The various layers of alloy may be rolled by conventional means in the art, such as hot rolling.
[0106] The alloys of the individual layers can be processed by relevant processes (eg sawing, milling).
[0107] After stacking the plate-shaped intermediate layer alloy, the core material layer alloy and the plate-shaped brazing layer alloy in sequence, they are compounded to obtain a composite body. It is understood by those skilled in the art that the stacking sequence can be designed according to the desired composite material. The relative position relationship of each plate-shaped alloy in the composite body is the same as the relative position relationship of the composite material finally obtained.
[0108] The composite is rolled to a target thickness. The rolling method may include hot rolling, cold rolling and a combination thereof. In one embodiment, a hot-rolled coil is rolled by multiple hot rolling passes, and the hot-rolled coil is further cold-rolled to the final finished product thickness. The total reduction of the hot-rolled coil is at least 70%, preferably 80% or more. During the cold rolling process, an intermediate annealing treatment may be performed. In one embodiment, an intermediate annealing treatment below 380°C is performed during the cold rolling process.
[0109] The obtained composite body of the final finished product thickness is subjected to soft annealing. Soft annealing can improve and reduce rolling oil residue, eliminate internal stress and reduce strength, and prevent cracking during subsequent processing. The temperature of soft annealing can be reasonably selected according to the specific composition of the aluminum alloy composite material for brazing. However, it should be lower than the melting temperature of the brazing material contained in the aluminum alloy composite material for brazing to avoid melting of the brazing material during soft annealing. In one embodiment, the temperature of soft annealing is 200°C-450°C.
[0110] The preparation method of the present invention can give the composite material the desired structure (multilayer structure, microscopic particle state) and material properties. The obtained composite material has high strength, excellent corrosion resistance, and can consume more waste materials, and is particularly suitable for making pipes for various heat exchangers with low carbon requirements.
[0111] Beneficial Effects
[0112] At present, the recycled aluminum brazing waste mainly involves process waste, and rarely involves waste after use by consumers (such as waste heat exchangers on scrapped cars). In addition, most of the reuse of aluminum brazing waste is changed to other uses and is no longer used for the production of aluminum brazing materials. Even if it is used to re-produce aluminum brazing materials, the corrosion resistance and brazing performance of the product are greatly reduced, and it can only be used in the lower-level aftermarket. The composite material of the present invention overcomes such problems. The composite material of the present invention uses a multilayer structure to replace the traditional two-layer or three-layer material, and optimizes the composition and proportion of each layer of material to obtain a material with both high strength and good corrosion resistance. The strength and corrosion resistance of the material are improved by regulating the microstructure in the core material layer and the intermediate layer. In the process of preparing the composite material of the present invention, a large amount of waste can be used, and the process waste generated in the preparation process and the post-consumer waste formed can be fully recycled without generating additional unusable waste, thereby realizing the self-circulation of the material. Green and sustainable development can be achieved, carbon emissions can be greatly reduced, and conditions for achieving the dual carbon strategy can be created.
[0113] Example
[0114] The solution of the present invention is further described in detail below in conjunction with specific embodiments.
[0115] It should be noted that the following examples are merely examples for clearly illustrating the technical solutions of the present invention, and are not intended to limit the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description, and it is not necessary and impossible to exhaustively list all the embodiments here, and the obvious changes or modifications derived therefrom are still within the scope of protection of the present invention. Unless otherwise specified, the instruments, equipment, and reagents used herein are all commercially available.
[0116] The samples of the embodiments and comparative examples of the present invention were prepared according to the following method:
[0117] The core layer alloy, the intermediate layer alloy and the brazing layer alloy with specific compositions are melted and cast respectively, wherein a certain amount of waste is added in the process of preparing each layer alloy;
[0118] The intermediate layer alloy is heat treated at a temperature of 350-550° C. and then hot rolled to form a plate-shaped intermediate layer alloy;
[0119] The brazing layer alloy is rolled into a plate-shaped brazing layer alloy, and then the core alloy ingot and each layer of the plate-shaped alloy are combined and loaded into a heating furnace for heating, and then the combined material is hot-rolled for multiple passes at 500° C. to be rolled into a 3.5 mm thick hot-rolled coil;
[0120] The hot rolled coil is further cold rolled to the finished thickness. The composite aluminum material of the finished thickness is annealed at a temperature above 200° C. to obtain the composite materials of each embodiment and comparative example.
[0121] The structures and components of each layer of the embodiment and comparative example are shown in Tables 1 and 2 below:
[0122] Table 1
[0123]
[0124] Table 2
[0125]
[0126] state * : HXX represents the state and hardness of the alloy, where H1-cold working hardening state; H2-tempering treatment after cold working hardening; the second digit after H represents the hardness level of the material;
[0127] Process waste output rate ** : Refers to the proportion of waste produced in the process of preparing composite materials to the total raw materials.
[0128] The composition of the produced process waste is calculated by the following formula, and the results are shown in Table 3 below:
[0129] Process waste composition = solder layer composition × solder layer composite rate % + first intermediate layer composition × intermediate layer composite rate % + core material layer composition × core material layer composite rate % + second intermediate layer composition × second intermediate layer composite rate %.
[0130] Taking Si element as an example, the Si content in the process waste = Si content in the brazing layer × the recombination rate of the brazing layer % + Si content in the first intermediate layer × the recombination rate of the first intermediate layer % + Si content in the core material layer × the recombination rate of the core material layer % + Si content in the second intermediate layer × the recombination rate of the second intermediate layer %.
[0131] Table 4 shows typical nominal compositions of post-consumer waste that may come from various types of heat exchangers, such as those in water tanks, condensers, intercoolers, oil coolers.
[0132] Table 5 shows the waste consumption of each embodiment and comparative example. The waste consumption rate in Table 5 indicates the proportion of the weight of the added waste to the weight of the core material layer in the process of preparing the core material. The HEX waste consumption rate refers to: the proportion of the weight of the added Hex waste to the weight of the core material layer in the process of preparing the core material. The self-generated process waste consumption rate refers to: the proportion of the weight of the added process waste to the weight of the core material layer in the process of preparing the core material of the composite material, wherein the added process waste is the waste generated in the process of preparing the composite material itself. Taking Example 1 in Table 5 as an example, the alloy of its core material layer is X1 alloy. In the process of preparing the composite material of Example 1, the output rate of the process waste (code F1) generated is 31%. All the produced process waste F1 is added to the process of preparing the X1 alloy, and a certain proportion of Hex waste and other alloy raw materials are added. The obtained X1 alloy can be used as the core material layer alloy of the composite material of Example 1. The total waste consumption rate is the sum of the process waste consumption rate and the post-consumer waste consumption rate.
[0133] It can be seen from the data in Table 5 that the total waste consumption rate in Examples 1-5 is relatively high, all being above 50%.
[0134] Table 3
[0135]
[0136] Table 4
[0137]
[0138] Table 5
[0139]
[0140] Waste consumption rate * : The weight of the waste added during the preparation of the core material layer accounts for the proportion of the weight of the core material layer.
[0141] Performance Testing
[0142] The composite materials of the embodiment and comparative example were subjected to brazing simulation: the temperature was raised from room temperature to 600°C in about 1 hour, and kept at this temperature for 3 minutes, cooled under nitrogen protection for 10 minutes, and then air-cooled to obtain the test materials after brazing simulation of the embodiment and comparative example. Then, each test material was evaluated according to the following method, and the results are shown in Tables 6-7.
[0143] 1. Strength test
[0144] The test materials after brazing simulation were prepared into tensile test specimens according to EN10002-1 standard, with a gauge length of 50 mm, and the tensile test was carried out at room temperature at a tensile speed of 20 mm / min.
[0145] 2. External corrosion test (SWAAT test)
[0146] The side of the test material after the brazing simulation that is away from the first intermediate layer is sealed, and the test is carried out according to ASTM G85 (A3) to measure the time for the material to be corroded and perforated.
[0147] 3. Internal corrosion (OY test)
[0148] The brazing layer side of the test material after brazing simulation was sealed in an atmosphere containing 195 ppm Cl - , 60ppm SO4 2- , 1ppmCu 2+ and 30ppm Fe 3+ The internal corrosion cycle test was carried out by placing the steel sheet in 88℃ high temperature water for 8 hours and then placing it at room temperature for 16 hours. The test time was 14 days. After the experiment, the depths of the 20 largest corrosion holes were measured and the average value was taken.
[0149] 4. Texture component measurement
[0150] The test materials after brazing simulation were then subjected to texture measurement and statistics by electron backscatter diffraction (EBSD).
[0151] 5. Particle density
[0152] After the test material was simulated brazed, the sample was sampled and prepared for scanning electron microscope observation. 20 samples with a size of 85 μm were selected. 2 The number of particles with equivalent diameters of 0.01 μm to 0.3 μm was counted in each area, and the particle density (particles / mm2) of the intermediate layer and core material of each test alloy was obtained. 3 ).
[0153] Table 6
[0154]
[0155] Table 7
[0156]
[0157] According to Table 6, the tensile strength of the brazed samples obtained in Examples 1-5 of the present invention is relatively high, all above 175 MPa.
[0158] The tensile strength of the brazed sample of Comparative Example 1 is only 115 MPa, which is significantly lower than that of the examples of the present application. The corrosion resistance (external corrosion and internal corrosion) of the composite materials of Examples 1-5 of the present invention is also significantly better than that of the sample of Comparative Example 1.
[0159] The thickness ratio of the intermediate layer of Comparative Example 2 is too low, and the corrosion resistance is relatively poor. Compared with Example 5, Comparative Example 3 has basically the same structure as Example 5, but the density of particles with an equivalent diameter of 0.01 μm-0.3 μm in the first intermediate layer of Comparative Example 3 is lower, and the ratio of the particle density in the first intermediate layer to the core material layer is lower. The tensile strength of Comparative Example 3 is significantly reduced, and the corrosion resistance is relatively worse.
[0160] In summary, the composite material of the present invention has excellent properties and a high waste consumption rate, and is particularly suitable for use as pipes for various heat exchangers with low carbon requirements.
Claims
1. A brazing aluminum alloy composite material, comprising: a core material layer, a first brazing layer, and a first intermediate layer, wherein: The first intermediate layer is located between the core material layer and the first brazing layer; Based on the total weight of the core material layer, the core material layer comprises: 0.6-1.5 wt% Si, 0.1-1.0 wt% Cu, 0.2-2.0 wt% Mn, 0.05-0.5 wt% Mg, 1 wt% or less Fe, 0.2 wt% or less Sr; at least one of the following elements: 0.5 wt% or less Zn, 0.05-0.25 wt% Ti, 0.05-0.25 wt% Zr and 0.05-0.25 wt% Cr; the balance is Al and unavoidable impurities; Based on the total weight of the first intermediate layer, the first intermediate layer comprises: 0.05-1.0 wt% Si, 0.6 wt% or less Fe, 1.0-1.5 wt% Mn, 0.1-2.5 wt% Zn; optionally one or more of the following elements: 0.5 wt% or less Cu, 0.25 wt% or less Ti, 0.25 wt% or less Zr and 0.25 wt% or less Cr; the balance is Al and unavoidable impurities; Based on the total weight of the first brazing layer, the first brazing layer comprises: 4-13 wt % Si, 0.05-2 wt % Cu, 0.05-6.00 wt % Zn, and the balance is Al and unavoidable impurities; The density of the dispersed particle phase with an equivalent diameter of 0.01-0.3 μm in the first intermediate layer is 7.5×10 10 -3.1×10 11 Pieces / mm 3 .
2. The aluminum alloy composite material for brazing according to claim 1, wherein The aluminum alloy composite material for brazing further comprises: a second intermediate layer, which is located on a side of the core material layer away from the first intermediate layer; Based on the total weight of the second intermediate layer, the second intermediate layer comprises: 0.05-1.0 wt% Si, 0.6 wt% or less Fe, 0.5-2.0 wt% Mn, 0.1-2.5 wt% Zn; optionally one or more of the following elements: 0.5 wt% or less Cu, 0.25 wt% or less Ti, 0.25 wt% or less Zr and 0.25 wt% or less Cr; the balance being Al and unavoidable impurities.
3. The aluminum alloy composite material for brazing according to claim 2, wherein: The aluminum alloy composite material for brazing further comprises: a second brazing layer, which is located on a side of the second intermediate layer away from the core material layer; Based on the total weight of the second brazing layer, the second brazing layer comprises: 4-13 wt % Si, 0.05-2 wt % Cu, 0.05-6.00 wt % Zn, and the balance is Al and inevitable impurities.
4. The aluminum alloy composite material for brazing according to claim 1, wherein The raw material of the core material layer comprises more than 50 wt % of waste materials based on the total weight of the raw material of the core material layer; wherein the waste material is selected from the group consisting of: post-consumer waste, process waste, and combinations thereof; The post-consumer waste comprises one or more of the following elements: 0.8-1.8 wt% Si, 1.0-1.6 wt% Mn; the post-consumer waste optionally further comprises one or more of the following elements: 0.1-0.6 wt% Cu, 0.2-0.7 wt% Zn, 0.02-0.15 wt% Mg; The process waste comprises one or more of the following elements: 0.7-3.0 wt. % Si, 0.8-1.5 wt. % Mn; the process waste optionally further comprises one or more of the following elements: 0.1-0.6 wt. % Cu, 0.03-1.3 wt. % Zn and 0.02-0.5 wt. % Mg.
5. The aluminum alloy composite material for brazing according to claim 4, wherein: The post-consumer waste is waste generated after the heat exchanger containing the brazing aluminum alloy composite material is scrapped; and / or The process waste is waste generated during the process of preparing the aluminum alloy composite material for brazing.
6. The aluminum alloy composite material for brazing according to claim 1, wherein The ratio of the density of the dispersed particle phase with an equivalent diameter of 0.01-0.3 μm in the first intermediate layer to the density of the dispersed particle phase with an equivalent diameter of 0.01-0.3 μm in the core material layer is 1-10.
7. The aluminum alloy composite material for brazing according to claim 2, wherein: The ratio of the density of the dispersed particle phase with an equivalent diameter of 0.01-0.3 μm in the second intermediate layer to the density of the dispersed particle phase with an equivalent diameter of 0.01-0.3 μm in the core material layer is 1-10.
8. The aluminum alloy composite material for brazing according to claim 2, wherein: The density of the dispersed particle phase with an equivalent diameter of 0.01-0.3 μm in the second intermediate layer is 1×10 10 -5×10 11 Pieces / mm 3 .
9. The aluminum alloy composite material for brazing according to claim 2, wherein: The second intermediate layer contains 1.0-1.5 wt% of Mn based on the weight of the second intermediate layer, and the density of the dispersed particle phase with an equivalent diameter of 0.01-0.3 μm in the second intermediate layer is 7.5×10 10 -3.1×10 11 Pieces / mm 3 .
10. The aluminum alloy composite material for brazing according to claim 1, wherein The density of the dispersed particle phase with an equivalent diameter of 0.01-0.3 μm in the core material layer is 5×10 9 -6×10 10 Pieces / mm 3 .
11. The aluminum alloy composite material for brazing according to claim 1, wherein After brazing, the total proportion of P texture and rotated cubic texture of the aluminum alloy composite material for brazing is more than 45%.
12. The aluminum alloy composite material for brazing according to claim 1, wherein The thickness of the first intermediate layer accounts for 5%-20% of the total thickness of the brazing aluminum alloy composite material; The thickness of the first brazing layer accounts for 5%-15% of the total thickness of the aluminum alloy composite material for brazing.
13. The aluminum alloy composite material for brazing according to claim 2, wherein: The thickness of the second intermediate layer accounts for 5%-20% of the total thickness of the aluminum alloy composite material for brazing.
14. The aluminum alloy composite material for brazing according to claim 3, wherein The thickness of the second brazing layer accounts for 5%-15% of the total thickness of the aluminum alloy composite material for brazing.
15. A method for manufacturing the aluminum alloy composite material for brazing according to any one of claims 1 to 14, comprising the following steps: preparing a core layer alloy, an intermediate layer alloy and a brazing layer alloy; The intermediate layer alloy is heat-treated and then rolled into a plate to obtain a plate-shaped intermediate layer alloy; the core layer alloy is optionally heat-treated; the brazing layer alloy is rolled into a plate to obtain a plate-shaped brazing layer alloy; After stacking the plate-shaped intermediate layer alloy, the core material layer alloy and the plate-shaped brazing layer alloy in sequence, they are compounded to obtain a composite body; rolling the composite body to a target thickness; Softening annealing.
16. The method of claim 15, wherein: Based on the weight of the core layer alloy, more than 50 weight percent of waste is added during the preparation of the core layer alloy; wherein the waste material is selected from the group consisting of: post-consumer waste, process waste, and combinations thereof; The post-consumer waste comprises one or more of the following elements: 0.8-1.8 wt% Si, 1.0-1.6 wt% Mn; the post-consumer waste optionally further comprises one or more of the following elements: 0.1-0.6 wt% Cu, 0.2-0.7 wt% Zn, 0.02-0.15 wt% Mg; The process waste comprises one or more of the following elements: 0.7-3.0 wt. % Si, 0.8-1.5 wt. % Mn; the process waste optionally further comprises one or more of the following elements: 0.1-0.6 wt. % Cu, 0.03-1.3 wt. % Zn and 0.02-0.5 wt. % Mg.
17. The method of claim 16, wherein: The post-consumer waste is waste generated after the heat exchanger containing the brazing aluminum alloy composite material is scrapped; and / or The process waste is waste generated during the process of preparing the aluminum alloy composite material for brazing.
18. The method of any one of claims 15 to 17, wherein The heat treatment temperature of the intermediate layer alloy is 350-550°C, and / or The heat treatment time of the intermediate layer alloy is 2-15 hours.
19. The method of claim 18, wherein: The heat treatment temperature of the intermediate layer alloy is 450-550°C.
Citation Information
Patent Citations
Al-Mg-Mn-Si series alloy, alloy plate strip and preparation method thereof
CN112210700A
Method of producing a clad aluminum alloy sheet for brazing purposes and sheet produced by said method
WO2007131727A1
Brazing aluminum alloy composite plate and production method thereof
CN103122427A
Cladded aluminum-alloy material and production method therefor, and heat exchanger using said cladded aluminum-alloy material and production method therefor
CN105814219A
Vacuum brazing fin material and preparation method thereof
CN109988946A